The Effect of Occlusal Loading on Gingival Microleakage of Bulk Fill Composites Compared with a Conventional Composite - Razieh Hoseinifar; Maryam Mofidi; Nima Malekhosseini (Shiraz University of Medical Sciences, 2020)
Statement of the Problem: Bulk fill composites have been introduced over the recent years in order to accelerate the process of tooth restoration by inserting composite in bulk up to 4mm thickness. Occlusal loading may influence the gingival microleakage of this composite. Purpose: This in vitro study aims to evaluate the effect of occlusal loading on the gingival microleakage of bulk fill composites compared with a conventional composite. Materials and Method: In this experimental study, box only class II cavities with gingival margins placed 1mm below the cemento-enamel junction were prepared on the mesial and distal surfaces of 36 maxillary premolars (72 cavities). The samples were divided into three groups and restored as follows: Group 1 (Tetric N-Ceram, incremental filling), Group 2 (X-tra fill, bulk filling), Group 3 (Tetric N-Ceram Bulk Fill, bulk filling). All restorations were thermocycled for 2000 cycles (5-50̊C) and then half of the samples were subjected to 200,000 cycles of loading. All the specimens were immersed in 0.5% basic fuchsin for 48 hours, then, sectioned, and evaluated for microleakage with a stereomicroscope. Data were analyzed using Kruskal-Wallis and Mann-Whitney U-tests. p< 0.05 was considered significant. Results: There were no significant differences among the gingival microleakage of three composites in both unloaded and loaded groups. In addition, no statistically significant difference was found between the microleakage of unloaded and loaded groups in all materials. Conclusion: Occlusal loading did not affect the gingival microleakage of bulk fill composites, and the microleakage of class II cavities restored with the bulk filling technique was similar to that of restored with the incremental technique.